Theoretical investigation of fullerene (C60) as nano carrier for anti-cancer drug Axitinib - Saied Jamaladdin Emamjome Koohbanani; Sayed Ali Ahmadi; Dadkhoda Ghazanfari; Enayatollah Sheikhhosseini (Carbon Trends, 2024)
Axitinib, marketed as Inlyta, finds various medical applications in the treatment of conditions such as breast cancer, myeloid leukemia, and juvenile myelomonocytic leukemia. Initially, the synthesis of this cytidine analog, and its deoxy derivative decitabine, was carried out in Czechoslovakia to explore their potential as chemotherapeutic agents for cancer treatment. Recent research has been focused on understanding the reactivity and chemical structure of Axitinib, which are believed to contribute to its anticancer properties. As part of this investigation, the adsorption process of Axitinib onto a fullerene (C60) adsorbent in the gas and water phases was examined using the DFT/B3LYP/6-311+G(d, p) method. This analysis involved the assessment of the adsorption energy and a chemical perspective on the interaction between Axitinib and the adsorbent molecule. Furthermore, various thermodynamic characteristics, including Gibbs free energy (-4004.73 kJ), Enthalpy (-4004.52 kJ), and Entropy (709.79 J/mol-kelvin), as well as thermodynamic capacity (349.69 J/mol-kelvin), were calculated. Additionally, key electronic parameters, such as σ(0.20), µ(-2.97), ω(0.88), χ(2.97), and η(5.01) (all in eV), were estimated to elucidate the compound's chemical properties. The calculation of the HOMO (-7.99 eV) and LUMO (2.04 eV) energy levels revealed six regions of chemical activity for Axitinib, confirming its thermodynamic stability and indicating the significance of this adsorption process in delivering Axitinib to biological mechanisms.